Google classroom as a tool for blended learning / Ainul Anuar Adam and Zulaikha Khairuddin - Anuar Adam, Ainul; Khairuddin, Zulaikha (Universiti Teknologi MARA, 2021)
Technology has moved forward and keep changing and evolved in times. Today, the education sector is introduced with Industrial Revolution 4.0 (IR 4.0), where it would be the latest journey for the education system. This study would like to identify students' perceptions on usefulness of Google Classroom for Blended Learning, determine students' perceptions on instruction delivery via Google Classroom for Blended Learning, and investigate students' satisfaction in learning via Google Classroom for Blended Learning. Quantitative approach was used in this study and there were 100 respondents who participate in this study. They were undergraduate students who were enrolled for ELC590: English for Oral Presentation course. It was found that students thought that using Google Classroom as useful to be implemented in the classroom. At the same time, they mentioned that student-teacher interaction was more interactive, and instructions given by the lecturers were well-delivered. They felt that using Google Classroom should be used more in the future. Thus, Google Classroom should be one of the platforms used by the educators to have better and more engagement with the students when they conduct blended learning or online session.